ANALISIS PENGARUH SHOPPING LIFESTYLE DAN FASHION INVOLVEMENT TERHADAP IMPULSE BUYING PADA PRODUK FASHION (Studi Kasus Pada Pengunjung Matahari Departement Store Pontianak) - Purmono- B11110079, Bintoro Bagus (Jurnal Manajemen Update, 2014)
The purpose of this research is to know influence of shopping lifestyle and fashion involvement against impulse buying both in partial and simultaneous. Respondents in research is all the visitors shopping fashion products at least twice in the Matahari department store pontianak in 2014, Old minimum of 17 years, And as the party that took a decision in the purchase of products fashion. Data collection method conducted by way of spreading the questionnaire to 100 people respondents through of purposive sampling techniques The analysis tools used is multiple linear regression. Based on the t test, obtained the result that in partial shopping lifestyle influential significantly to impulse buying with a value of t count as much as 4,216Â  and value of significance 0,000, while fashion involvement get t value count as much as 2.368 and value of significance 0.020. Based on the F test, Obtained the result that simultaneously shopping lifestyle and fashion involvement influential significantly to impulse buying with a value of F count as much as 50.094 and value of significance 0,000. The value of the coefficients determination of shopping lifestyle and fashion involvement against impulse buying as much as 50,8 %, the remaining amounting to 49.2 % influenced by other variables that are not investigated in this research. Keywords: Shopping Life Style, Fashion Involvement and Impulse Buying.